2005
DOI: 10.1080/08035320510028058
|View full text |Cite
|
Sign up to set email alerts
|

Fabry disease and the heart: an overview of the natural history and the effect of enzyme replacement therapy

Abstract: Fabry disease is a genetic disorder caused by the deficiency of a-galactosidase A, resulting in the lysosomal accumulation of glycosphingolipids. Fabry disease may result in cardiac, cerebral and renal complications. Cardiac abnormalities in patients with Fabry disease were first described in the 1960s. In the 1990s a form of Fabry disease confined to the heart was reported; however, this variant is extremely rare and a more appropriate concept is of cardiac predominance of the disease in some patients. Up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 24 publications
0
6
0
3
Order By: Relevance
“…Thus, the technology has been extended from the theoretical concept of a common platform used for diagnosis to a sensitive technology that can used for large-scale screening of newborns independently of selection by clinical symptoms. This is of clinical importance because the disorders of Gaucher, Fabry, MPS I and Pompe currently have available, for clinical use or trials, enzyme replacement therapy that either has been demonstrated to improve (Gaucher, Fabry;Scott et al 2003;Shah and Elliott 2005) or is expected to improve (MPS I, Pompe;Desnick 2004;Miebach 2005) the clinical status of affected individuals. In the case of Krabbe and Niemann-Pick disease, there is evidence that presymptomatic detection and intervention by the use of umbilical stem cell transplantation markedly improves the clinical course of the disease (Escolar et al 2005;Krivit 2004).…”
Section: Assays For Enzyme Deficiencies: Lysosomal Storage Disordersmentioning
confidence: 99%
“…Thus, the technology has been extended from the theoretical concept of a common platform used for diagnosis to a sensitive technology that can used for large-scale screening of newborns independently of selection by clinical symptoms. This is of clinical importance because the disorders of Gaucher, Fabry, MPS I and Pompe currently have available, for clinical use or trials, enzyme replacement therapy that either has been demonstrated to improve (Gaucher, Fabry;Scott et al 2003;Shah and Elliott 2005) or is expected to improve (MPS I, Pompe;Desnick 2004;Miebach 2005) the clinical status of affected individuals. In the case of Krabbe and Niemann-Pick disease, there is evidence that presymptomatic detection and intervention by the use of umbilical stem cell transplantation markedly improves the clinical course of the disease (Escolar et al 2005;Krivit 2004).…”
Section: Assays For Enzyme Deficiencies: Lysosomal Storage Disordersmentioning
confidence: 99%
“…1 Affected patients have an impaired ability to degrade membrane glycosphingolipids containing a terminal ␣-glycosidic galactose, especially globotriaosylceramide/ceramide trihexoside (GL 3 ), which accumulates in tissues. Storage in the vascular endothelium increases the risk for cerebrovascular accidents (CVA) and myocardial microvascular ischemia [2][3][4] ; in the heart causes dysrhythmias, hypertrophic cardiomyopathy, and valvular insufficiency 5 ; in the kidney leads to progressive renal insufficiency and eventually failure 6 ; in the peripheral nervous system gives rise to gastrointestinal dysmotility, hypohidrosis, temperature intolerance, dysregulation of vascular tone, and characteristic acroparesthesias of the hands and feet. [7][8][9] Obstructive lung disease and impaired exercise tolerance are also seen.…”
mentioning
confidence: 99%
“…Les patients à risque de mort subite, si redouté, ne représentent que moins de 5 % de l'ensemble de la population des CMH et, globalement, la survie à long terme pour la majorité des patients n'est pas très différente de celle de la population générale, du moins pour les formes autosomiques dominantes. Ainsi, pour une présentation initiale qui peut être similaire, les pronostics de ces maladies sont très différents : le plus souvent favorables dans la CMH, cause majeure de décès avec une réduction de l'espérance de vie de 15 à 20 ans dans la maladie de Fabry [1,2,4].…”
Section: Un Problème De Définitionunclassified
“…L'atteinte cardiaque de la maladie de Fabry est très fréquente, non spécifique (HVG chez plus de 70 % des cas après l'âge de 30 ans, fuite mitrale, blocs de branche ou auriculo-ventriculaire, PR court, coronaropathie, insuffisance cardiaque…). Elle peut être isolée avec HVG progressive et sévère chez les hommes hémizygotes comme chez les femmes hétérozygotes [4,5]. Le réel problème en milieu cardiologique adulte est le diagnostic d'une HVG sans cause identifiée se présentant comme une maladie cardiaque isolée ou largement prédominante.…”
Section: Un Problème Diagnostiqueunclassified